Analyzing Gastronomy Influencers’ Views about Gastronomy Tourism - Isevcan Ertamay, Selin; Güler, Mehmet Emre (International Journal of Contemporary Economics and Administrative Sciences, 2024)
In recent years, there has been a growing interest towards gastronomic tourism worldwide. The unique gastronomic offerings of a destination are getting a pivotal attraction for travelers. This qualitative research aims to provide an assessment of how the gastronomy tourism was affected by Covid-19 and explore future trends and potential strategies for the growth of gastronomy tourism after pandemic from the perspective of gastronomy social media influencers in Turkey through in-depth interviews. The qualitative data was analyzed through thematic analysis with systematically condensing extensive text data into organized summaries of key findings. The findings demonstrate an understanding to determine what needs to stay the same and what needs to change after Covid-19 in order to promote the revival of gastronomy tourism. Findings highlights safety and socio-psychological needs of tourists, the role of social media, critics in adaptation to technology, new trends and economic conditions, emphasizing the growing demand for local and authentic experiences. The original aspect of this research is that it presents a holistic perspective by investigating influencers’ views on all the parts and stakeholders of gastronomy tourism and its future, considering the impact of the Covid-19 pandemic.